The effects of Transcendental Meditation on emotional intelligence, stress, fatigue, and sleep quality among Ayurvedic medical students in India - Paredes, Carol; Nidich, Sandy; Yeola, Gunvant; Wele, Asmita; Kamble, Santosh; Tehre, Kamalakar; Wallace, Robert Keith; Rainforth, Maxwell (Frontiers in Education, 2025)
IntroductionEmotional intelligence (EI) is essential for resilience and adaptability in high-pressure environments such as medical education. Transcendental Meditation (TM) has been shown to enhance emotional regulation, reduce stress, and improve wellbeing. This quasi-experimental, longitudinal observational study evaluated the effects of TM on emotional intelligence, perceived stress, fatigue, and sleep quality among Ayurvedic medical students over a 6-month period.MethodsThis study included 176 Ayurvedic medical students at D. Y. Patil College of Ayurved and Research Center of Dr. D. Y. Patil Vidyapeeth (Deemed to be University) in India, comprising a TM group (n = 97) and a control group (n = 79). Global Emotional Intelligence (Global EI) and its subdomains (Wellbeing, Emotionality, Self-Control, and Sociability) were assessed using the Trait Emotional Intelligence Questionnaire, Short Form (TEIQue-SF). Secondary outcomes included perceived stress (Perceived Stress Scale; PSS), fatigue (PROMIS Fatigue Short Form), and insomnia severity (Insomnia Severity Index; ISI). Assessments were conducted at baseline, 3 months, and 6 months. Linear mixed-effects models (LMMs) were used to evaluate Group × Time interactions for each outcome, controlling for age. An autoregressive [AR(1)] covariance structure was specified to account for repeated measures. Pairwise comparisons based on estimated marginal means were used to assess between-group differences at each timepoint.ResultsSignificant Group × Time interactions were observed for Global Emotional Intelligence (EI) (p < 0.001), perceived stress (p < 0.001), fatigue (p < 0.001), and insomnia severity (p < 0.001), indicating that the TM and control groups showed different patterns of change over time. Specifically, the TM group demonstrated substantial improvements in Global EI and significant reductions in perceived stress, fatigue, and insomnia severity by 6 months compared to the control group. Secondary analyses also revealed significant Group × Time interactions across all four Global EI subdomains (Wellbeing, Emotionality, Self-Control, and Sociability; all p < 0.001).ConclusionRegular practice of Transcendental Meditation (TM) led to meaningful improvements in emotional intelligence, reductions in perceived stress and fatigue, and enhanced sleep quality among Ayurvedic medical students. These findings support integrating TM into student wellness programs as an effective strategy for promoting psychological resilience in high-stress academic environments.